Monstrous beings and media cultures : folk monsters, im/materiality, regionality - Balanzategui, Jessica; Craven, Allison (Amsterdam University Press, 2023)
Monstrous Beings of Media Cultures examines the monsters and sinister creatures that spawn from folk horror, Gothic fiction, and from various sectors of media cultures. The collection illuminates how folk monsters form across different art and media traditions, and interrogates the 21C revitalization of "folk" as both a cultural formation and aesthetic mode. The essays explore how combinations of vernacular and institutional creative processes shape the folkloric and/or folkoresque attributes of monstrous beings, their popularity, and the contexts in which they are received. While it focuses on 21C permutations of folk monstrosity, the collection is transhistorical in approach, featuring chapters that focus on contemporary folk monsters, historical antecedents, and the pre-C21st art and media traditions that shaped enduring monstrous beings. The collection also illuminates how folk monsters and folk "horror" travel across cultures, media, and time periods, and how iconic monsters are tethered to yet repeatedly become unanchored from material and regional contexts.
"Amsterdam University Press"
Keywords: Monsters -- Folklore.; Monsters in mass media.; Monsters in popular culture.; Monstres -- Folklore.; Monstres dans les médias.; Monstres dans la culture populaire.; Film: styles and genres.; Classic horror and ghost stories.; PERFORMING ARTS / Film / Genres / Horror.; SOCIAL SCIENCE / Folklore & Mythology.; Monsters.; Horror and supernatural fiction.; Folklore, myths and legends.; Mythical and legendary beings, monsters and creatures.; Film, Media, and Communication; FMC; Cultural Studies; CULTURAL; Interdisciplinary Studies; INTERDISC; Media Studies; MEDIA; Psychology; PSYCH; Monsters, folk, immateriality, regionality, folkloresque, Gothic; Folklore.